Study on the Knowledge, Attitude and Behavior of College Students in Guangxi Province, China during Covid-19 Pandemic - Hui Chen, Luwen Gan, Zhenyou Guo, Fengyi Ma (Forest Chemicals Review)
COVID-19 has rapidly spread through countries .This occurrence has resulted in a huge negative response from the general public; the media continuously disseminate information to keep everyone notified regarding this global pandemic state. Public education is considered one of the most important measures that might help control COVID-19. This research assessed COVID-19 knowledge, attitude, and behaviour among college students in Guangxi Province, China. A cross-sectional survey-based that was conducted online on March 16, 2020 to May 4, 2020 among College students from Guangxi Province, China. The electronic survey devised by the researchers includes four main segments relating to the profile of the participants, knowledge, attitude and behavior during the novel coronavirus pandemic. The study data revealed that the respondents had an adequate level of knowledge about the mode of transmission, symptoms and prevention strategies on COVID-19. The survey likewise illustrated an overall positive attitude and behavior toward these protective measures for the virus and its responses if an infection was contracted. Also, Majority of the students don’t consider the virus as a stigma or hide it from medical specialists. They avoid the situation where they can get COVID-19 and chose to seek medical treatment or isolate themselves if needed. The current study showed enough knowledge, positive behaviour and moderate attitude towards COVID-19 among the students. This response indicates the impact of the official statement confirmed by the WHO about COVID-19 being a disease outbreak and the initiatives of the health officials to notify and educate the public regarding this pandemic. Nonetheless, most research participants displayed satisfactory responses to COVID-19 knowledge behaviour and attitudes, implying the effectiveness of the awareness campaigns. The findings of the study may prove to be the basis for preparing government programs, policies and plans to adequately manage COVID-19 and to limit its transmission.